Teacher and Student Practices Associated with Performance in the PISA Reading Literacy Evaluation - Rojas-Torres, Luis; Ordóñez, Graciela; Calvo, Karen (Frontiers in Education, 2021)
This article aims at finding teacher and student practices that relate to performance in PISA reading literacy evaluations and that are feasible to intervene in order to assist the improvement of reading competency. To achieve this purpose, the study was developed with data collected from the population of Costa Rica that took the PISA evaluation in 2018 (n=4691, 2340 men, and 2351 women). A linear regression of the reading score was performed utilizing plausible values and sampling weights. The predictors of the regression were contextual factors, teacher practices, and student habits. Time spent and interest in reading showed a positive and relevant association with student performance in reading, controlling important background aspects like economic resources and parents' education. Moreover, 28.19% to the obtained variance explanation of the reading literacy was only due to the teacher and student practices. These results provide favorable information to design interventions for the improvement of reading competency.